The clinical and educational outcomes of an inter-professional student-led medication review team, a pilot study - Michael O. Reumerman; Milan C. Richir; Philippe M. Domela Nieuwenhuis; Rowan Sultan; Hester E. M. Daelmans; Hans Springer; Majon Muller; Michiel A. van Agtmael; Jelle Tichelaar (European Journal of Clinical Pharmacology, 2021)
Aims The involvement of an inter-professional healthcare student team in the review of medications used by geriatric patients could not only provide patients with optimized therapy but also provide students with a valuable inter-professional learning experience. We describe and evaluate the clinical and learning outcomes of an inter-professional student-run mediation review program (ISP). Subject and method A variable team consisting of students in medicine, pharmacy, master advanced nursing practice, and master physician assistant reviewed the medication lists of patients attending a specialized geriatric outpatient clinic. Results During 32 outpatient visits, 188 medications were reviewed. The students identified 14 medication-related problems, of which 4 were not recognized by healthcare professionals. The ISP team advised 95 medication changes, of which 68 (71.6%) were directly implemented. Students evaluated this pilot program positively and considered it educational (median score 4 out of 5) and thought it would contribute to their future inter-professional relationships. Conclusion An inter-professional team of healthcare students is an innovative healthcare improvement for (academic) hospitals to increase medication safety. Most formulated advices were directly incorporated in daily practice and could prevent future medication-related harm. The ISP also offers students a first opportunity to work in an inter-professional manner and get insight into the perspectives and qualities of their future colleagues.

Partial fusion of basic granulites at 5 to 15 kbar: implications for the origin of TTG magmas - Wilhelm Springer; Hans Adolf Seck (Contributions to Mineralogy and Petrology, 1997)